Component‐based quantification and prediction of diet selection by cattle grazing on multi‐species communities. (16th October 2015) - Tsutsumi, Michio; Takahashi, Yoshitaka; Emoto, Shigeki; Ito, Naoya; Otani, Ichiro; Matsumoto, Kazunori
Abstract: Quantification and prediction of diet selection by animals grazing on forage with mixed‐species composition is challenging. The objective of this study was to establish a method to predict the nutritive value of the selected diet in cattle grazing on multi‐species plant communities. The nutrient concentrations in the selected diet and forage on offer were evaluated, and the relationship between these nutrient concentrations and the forage utilization rate was analyzed. Short‐term grazing experiments were performed on abandoned cultivated land, without seeding or fertilizer. Before and after each grazing session, the forage was harvested and analyzed to determine concentrations of crude protein (CP), neutral detergent fiber (aNDFom), acid detergent fiber (ADFom) and lignin. The nutrient concentrations on offer and in the selected diet, and the forage utilization rate were calculated based on the apparent disappearance during each experiment. Cattle selected a diet with, on average, 12.0% higher CP and 4.4–13.0% lower aNDFom, ADFom and lignin concentrations than those of forage on offer, and the selectivity depended on the forage utilization rate. The nutrient concentrations in the selected diet were then predicted using only the information on the offered forage. The aNDFom concentration in the selected diet could be accurately predicted, and the concentrations of CP, ADFom and lignin in the selected diet could be roughly predicted. The significant correlations between selectivity for each component and forage utilization rate were used to construct estimation models. Combining the forage utilization rate and the nutrient concentration on offer improved the accuracy of predicting the CP concentration in the selected diet. However, it had little effect on the accuracy of the predictions of aNDFom, ADFom or lignin concentrations in the selected diet.